THE PERCEPTION OF STAKEHOLDERS TO THE ROLE OF GRADUATE OF RELIGIOUS STUDY TO RELIGIOUS HARMONY IN MEDAN CITY - Muhammad Jailani; Elly Warnisyah Harahap (State Islamic University of North Sumatra Indonesia, 2019)
This research is to describe a perception and an expectation of stakeholders to the role of the graduate of the study of religions in creating the harmony of religious people. The background of this study is the responsibility of The State Islamic University of North Sumatra, especially the study program of study of religions to contribute in creating the harmony and to resolve the conflict among religious people in Indonesia. On the other hand, this study program is never been evaluated since being established. The study location is in Medan city which is a plural city and a high risk of conflict. The research subject is the government representative, representative of religious scholars, religious instructor, interfaith practitioners, and lecturer. This research basically uses a quantitative descriptive method. However, in explanation of numerics and the description of stakeholders’ expectation, it uses the qualitative approach. The theories of role, and perception are discussed. Conceptual framework and operational definition are discussed. This study finds that the perception of stakeholders is very positive to the graduate of the study of religion on their role to create the harmony of religious people. Nevertheless, among perception of knowledge, attitude, and skill, the perception of stakeholder on the skill of graduate is the lowest. The skill in creating harmony is a skill of analysis, development, communication, and management. It needs an attention from the University to improve the curricula and learning method. The expectations of stakeholders are also discussed. Keywords: Religious Harmony, Role of Graduated Study of Religion, Perception, Expectation,Skill, attitude and knowledge